EKSTRAK DAUN UBI JALAR UNGU SEBAGAI ANTIOKSIDAN UNTUK MEMPERLAMBAT KETENGIKAN (RANCIDITAS) PADA MINYAK KELAPA - Dwi Putri Rejeki (Lantanida Journal, 2018)
The study of purple sweet potato leaf extract as an antioxidant to slow down rancidity in coconut oil has been conducted. The aim of this study was to prove the addition of purple sweet potato leaf extract to postpone the rancidity of coconut oil. The sample used in this study was coconut oil taken from the village of Tingkeum Lampeuneurut, Aceh Besar District, as much as 300 mL. The sample was divided into two Erlenmeyers with 150 ml in each and heated to 90°C of temperature. After that, the first Erlenmeyer was added by 30 ml of purple sweet potato leaf extract. Then, the second Erlenmeyer was chilled and left in open air for 5 days. The sample that was not added by purple sweet potato leaf extract was set as a control. Several parameters were tested in both samples, namely an iodine number, peroxide number, free fatty acid and saponification number. The results were obtained by the addition of purple sweet potato leaf extract and control oil respectively the iodine number 10.21 and 7.54 g I2/100 g samples, peroxide numbers 4.67 and 9.33 mg O2/g, free fatty acids 8.87 and 8.67%, acid numbers 24.2 and 23.5 mg KOH/g, saponification 230.49 and 234.09 mg KOH/g, esters 206.29 and 210.59 mg KOH/g. The peroxide number of oilwhich was added by the purple sweet potato leaf extract has been fulfilled the SNI for coconut oil while the control oil does not. Meanwhile the iodine numbers, acid numbers, saponification numbers, and free fatty acids in both oils do not fulfill the SNI. Based on this study was obtained that the purple sweet potato leaf extract can postpone the rancidity caused by oxidation by reducing the peroxide number. However, the purple sweet potato leaf extract was not able to inhibit the increasing of acid numbers or free fatty acids caused by hydrolysis reactions.